2017
DOI: 10.1080/00325481.2017.1385365
|View full text |Cite
|
Sign up to set email alerts
|

Can pleiotropic effects of eicosapentaenoic acid (EPA) impact residual cardiovascular risk?

Abstract: Residual cardiovascular (CV) risk persists even in statin-treated patients with optimized low-density lipoprotein cholesterol (LDL-C) levels. Other pathways beyond cholesterol contribute to CV risk and the key to reducing residual risk may be addressing non-cholesterol risk factors through pleiotropic mechanisms. The purpose of this review is to examine the literature relating to the potential role of the omega-3 fatty acid eicosapentaenoic acid (EPA) in reducing residual CV risk. The literature shows that EPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…On consideration, the clinical benefits in REDUCE-IT seemed to exceed what would be expected from the 20% reduction in TG levels seen with icosapent ethyl. This idea is further supported by the observation that benefits were independent of baseline TG levels, and suggests that other mechanisms possibly contributed to the benefits (54). These include an anti-inflammatory effect because high-sensitivity C-reactive protein was lower by approximately 40% in the icosapent ethyl treated patients compared with the placebo group.…”
Section: Omega-3 Fatty Acidsmentioning
confidence: 78%
“…On consideration, the clinical benefits in REDUCE-IT seemed to exceed what would be expected from the 20% reduction in TG levels seen with icosapent ethyl. This idea is further supported by the observation that benefits were independent of baseline TG levels, and suggests that other mechanisms possibly contributed to the benefits (54). These include an anti-inflammatory effect because high-sensitivity C-reactive protein was lower by approximately 40% in the icosapent ethyl treated patients compared with the placebo group.…”
Section: Omega-3 Fatty Acidsmentioning
confidence: 78%
“…Reported biological actions of EPA and DHA extend well beyond TG lowering and include effects expected to be cardioprotective . As summarized by Mozaffarian and Rimm, and shown in Figure , fish oil omega‐3 PUFAs have been linked with reduced blood pressure and heart rate, as well as decreased platelet aggregation .…”
Section: Residual Riskmentioning
confidence: 97%
“…Differences in OM-3 fatty acid composition may also have contributed to disparate CVOT findings. It is possible that, beyond TG lowering, pleiotropic effects of EPA on other lipids/ lipoproteins, inflammation, oxidation, phospholipid membranes, and plaque [2] may have contributed to the CV risk reduction demonstrated in JELIS, REDUCE-IT, and other smaller trials [29]. In light of the recent OM-3 dietary supplement CVOT data [25], the European Medicines Agency Committee for Medicinal Products for Human Use concluded that DHA ?…”
Section: Key Om-3 Cvotsmentioning
confidence: 99%
“…The omega-3 (OM-3) fatty acids eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) may have a preventive role in the development and progression of atherosclerotic cardiovascular disease (ASCVD) [1][2][3][4]. While both EPA and DHA reduce triglycerides (TG), DHA may raise low-density lipoprotein cholesterol (LDL-C) [5,6].…”
Section: Introductionmentioning
confidence: 99%